Population and Feeding Ecology of Parapenaeopsis scuiptilis (Heller, 1862) in Klang Strait, Peninsular Malaysia - I, Masitah; V.C, Chong (Malaysian Journal of Science, 2002)
A study of the population and feeding ecology of the marine prawn Parapenaeopsis sculptilis was conducted at the mudflat off Sungai Buloh and on an offshore shoal (Angsa Bank) in the Kiang Strait. The female:male sex ratio varied with the month of sampling with a range of 0.80-18.00. P. sculptilis showed negative allometric growth. Size at sexual maturity for P. sculptilis occurs at 16 mm for male and 25 mm for female. Mating and spawning could have occurred in shallow inshore water. Population densities were high at Angsa Bank and on the mudflat with mean densities of 2,246 and 1,137 individuals per hectare, respectively. Fifty-three to 68% of the prawns sampled were juveniles of 10-25 mm carapace length, indicating that the study sites function as important nursery areas. Stomach-content analysis revealed no significant diet difference between juvenile and adult prawns which fed on a variety of food comprising mainly mangrove detritus, crustaceans and molluscs.